2010
DOI: 10.1590/s0100-69162010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros de dimensionamento para biodigestores batelada operados com dejetos de vacas leiteiras com e sem uso de inóculo

Abstract: RESUMO:Objetivou-se avaliar a adição de inóculo na biodigestão anaeróbia de dejetos de vacas leiteiras reciclados em biodigestores bateladas pela quantidade de biogás produzida, pela redução dos sólidos voláteis e pelos potenciais de produção de biogás para obtenção de parâmetros de dimensionamento. Foram utilizados 12 biodigestores bateladas de campo de 60 L, cujos substratos continham dejetos de vacas leiteiras, água e quatro adições de inóculo (0; 20; 30 e 40% v/v). Adotaram-se tempos médios de retenção hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
20

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
1
12
0
20
Order By: Relevance
“…Larger biogas production can be achieved with the addition of inoculum from the beginning of the anaerobic biodigestion process. According to a study by Xavier & Lucas Junior (2010), higher biogas production potentials were obtained with the use of 40% of inoculum in biodigesters using dairy cows manure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger biogas production can be achieved with the addition of inoculum from the beginning of the anaerobic biodigestion process. According to a study by Xavier & Lucas Junior (2010), higher biogas production potentials were obtained with the use of 40% of inoculum in biodigesters using dairy cows manure.…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed a biogas average production of 3L/kg of substrate, higher than that observed in the present study. Xavier & Lucas Junior (2010) evaluated the biogas production and the reduction of volatile solids from the addition of inoculum in the anaerobic biodigestion of recycled waste of dairy cows in batch biodigesters with a capacity of 60 L. The authors observed a biogas production of 70 L/kg of substrate with the hydraulic retention time of 45 days. According to the authors, the use of inoculum is a method used to increase biogas production, which consists in adding to the material to be digested, a material that has already undergone the biodigestion process, providing an additional population of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Inoculum consisted of iodine, derived from the municipal sewage treatment system, with approximately 4% total solids. The use of 40% (m m -1 ) inoculum of the total sample volume was based on studies by Xavier and Lucas Jr. (2010).…”
Section: Methodsmentioning
confidence: 99%
“…0.254 and 0.627 m 3 ·kg·VS added -1 (Orrico et al, 2004;Xavier et al, 2010;Sakar et al, 2009;Miranda et al, 2012), respectively. Thus, manipueira incremented biogas yield in 26 ruminants and 31 % when co-digested with sheep and swine manure, respectively.…”
Section: Substratesmentioning
confidence: 99%